Social Media and teaching in Postgraduate - Román San Miguel, Aránzazu (Historia y Comunicación Social, 2014)
The use of social networking in the university can be a great ally in teaching and learning. And this in two ways, in the workplace to carry out the profession and in the research to know what happens in the society in which it operates the researcher, especially when we talk about the field of social sciences. In this paper we analyze the importance of using social networks in the university, focusing on the Master’s Degree in Corporate Communications and Policy at the University of Seville.
Keywords: Social networking; teaching; postgraduate; university; professional field; reseach